2020
DOI: 10.3390/pharmaceutics12030282
|View full text |Cite
|
Sign up to set email alerts
|

Topical Delivery of Meloxicam using Liposome and Microemulsion Formulation Approaches

Abstract: The aim of this study is to develop, characterize and compare conventional liposome, deformable liposome (transfersome) and microemulsion formulations as potential topical delivery systems for meloxicam. Liposomes were characterized in terms of vesicle size, zeta potential and entrapment efficiency. For microemulsions, particle size, electrical conductivity and viscosity studies were performed to assess the structure of the investigated systems. An ex vivo skin permeation study has been conducted to compare th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 66 publications
1
31
1
2
Order By: Relevance
“…Particle diameters of 10−200 nm are most relevant for exerting biological effects [ 33 ]. For lipid-based nanoparticles, a PDI of ≤ 0.3 is considered to be acceptable [ 34 ]. Our nanosystems showed a PDI of 0.42, and they can be considered highly polydisperse [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Particle diameters of 10−200 nm are most relevant for exerting biological effects [ 33 ]. For lipid-based nanoparticles, a PDI of ≤ 0.3 is considered to be acceptable [ 34 ]. Our nanosystems showed a PDI of 0.42, and they can be considered highly polydisperse [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…The formulations developed in the previous studies 14,15 had low MX content, so the resulting gel formulations did not yield any meaningful permeation results. Therefore, we modified the liposomal formulations as summarized in Table 1 in the present study to increase the content of MX.…”
Section: Characterization Of Mx-loaded Liposomesmentioning
confidence: 92%
“…In order to improve its solubility and lipophilicity, one of the available options is to encapsulate the MX in a liposomal formulation that will improve the solubility and permeability through Stratum corneum . In our previous studies, we have used both transfersomes 14 and flavosomes 15 to encapsulate MX and observed improved solubility and skin permeability of MX into the deeper layers of human skin. Transfersomes are considered the first generation of deformable vesicles developed by Cevc and Blume 16 and Cevc et al, 17 They are generally prepared by addition of a surfactant (edge activator) into the conventional liposomes.…”
Section: Introductionmentioning
confidence: 99%
“…Under stress conditions, EA relocates in the areas with higher curvature. 25,26 Other types of liposomes can be prepared and characterized following the same methodology as for conventional liposomes, as will be discussed later.…”
Section: Ultradeformable Liposomesmentioning
confidence: 99%
“…The particle size is going to play an important role in terms of skin delivery because it affects the penetration of encapsulated compounds through the skin to the deeper layers. 26,40 MPPC, monopalmitoyl-2-hydroxy-sn-glycero-3-phosphocholine; P80, Polysorbate 80; PDI, Polydispersity Index; PC, phosphatidylcholine; SL, soybean lecithin; SPC, soy phosphatidylcholine; S80, Span 80; SC, sodium cholate; SM, sorbitan monooleate; T80, Tween 80; TEM, transmission electron microscopy; YL, yolk lecithin; w/w, weight/weight.…”
Section: Particle Size Reductionmentioning
confidence: 99%